Education, immigration and migration : revisiting and re-imagining policy, leadership and praxis for a changing world - Arar, Khalid; Crawford, Emily R.; Örücü, Deniz; Bogotch, Ira (Emerald Publishing Limited, 2025)
This timely second edition of Education, Immigration and Migration offers new insights into the ways that educational leaders, policy makers, students, teachers and community members are changing their practice in light of global migration. Including research-based chapters that touch on both local idiosyncrasies and dynamics common across many contexts, chapter authors identify issues educational leaders face as they seek to lead schools and school systems experiencing immigration and better understand their current strategies for improvement. As the relationship between educational leadership and immigration/refugee populations is not fully understood, this updated edition will help readers gain a deeper appreciation of the scope and nature of issues at local, national and transnational levels. In doing so, authors discuss "what is working" and "what is not working," allowing for a sharing of ideas and approaches across borders. Chapters utilize cross-disciplinary frameworks, global-national data sets, NGO reports, and descriptions of local practices in educational leadership related to the education of immigrants, migrants, refugees and asylum seekers. Documenting these journeys and influences is vital to expanding the conceptual frameworks of educational leadership as a field of study beyond managing schools. In hopes of drawing attention and awakening the field of educational leadership to the influences of [im]migration as a focal point, this volume will be of interest to state and local policymakers, educational schools, and university leaders as well as educational researchers.
Keywords: Immigrant children -- Education.; Refugee children -- Education.; Education -- Educational Policy & Reform -- General.; Educational administration and organization.; Educational strategies and policy.; elektronické knihy; electronic books